Ten-year experience with testicular cancer at a tertiary care hospital in a resource-limited setting: a single centre experience in Tanzania - Chalya, Phillipo L (World J Surg Oncol, 2014)
BACKGROUND: Testicular cancers constitute major therapeutic challenges in resource-limited countries and still carry poor outcomes. There is a paucity of published data regarding testicular cancer in Tanzania, and Bugando Medical Centre in particular. This study describes the clinicopathological pattern, treatment outcome and challenges in the management of testicular cancer in our local setting. METHODS: This was a retrospective study including all patients who had had histopathologically confirmed testicular cancer at Bugando Medical Centre between February 2004 and January 2014. RESULTS: A total of 56 testicular cancer patients were enrolled in the study, representing 0.9% of all malignancies. The median age of patients at presentation was 28 years, with a peak incidence in the 21-to-30-year age group. A family history of testicular cancer was reported in four (5.4%) patients. A history of cryptorchidism was reported in six (10.7%) patients. Most patients (57.1%) presented late with an advanced stage of cancer. Testicular swelling was the main complaint in 48 (85.7%) patients. The right testis was involved in 67.9% of cases. Lymph node and distant metastases were documented in 10 (17.9%) and 12 (21.4%) patients, respectively. Histologically, 80.4% of patients had germ cell cancers, with seminoma accounting for 62.2% of cases. The most common surgical procedure was inguinal orchidectomy (77.4%). Adjuvant chemotherapy and radiotherapy were used in six (11.1%) and four (7.4%) patients, respectively. Eight (14.3%) patients died. The main predictors of mortality (P < 0.001) were patient’s age (>65 years), late presentation (>6 months), stage of disease, and presence of metastasis at time of diagnosis. The mean follow-up period was 22 months. At the end of five years, only 18 (37.5%) patients were available for follow-up and the overall 5-year survival rate was 22.2%. The main predictors of 5-year survival rate (P < 0.001) were patients’ age, stage of disease, and presence of lymph node and distant metastases. CONCLUSIONS: Testicular cancers, though rare in our setting, still carries a poor prognosis. Late presentation, poverty, paucity of resources and the high cost of newer imaging and treatment modalities are major challenges to management. Better health funding and education regarding testicular self-examination is essential.